A Twist‐Bend Nematic Phase Driven by Hydrogen Bonding1. (17th November 2014) - Jansze, Suzanne M.; Martínez‐Felipe, Alfonso; Storey, John M. D.; Marcelis, Antonius T. M.; Imrie, Corrie T.
Abstract The liquid crystalline phase behavior of 4‐[6‐(4′‐cyanobiphenyl‐4‐yl)hexyloxy]benzoic acid (CB6OBA) and 4‐[5‐(4′‐cyanobiphenyl‐4‐yloxy)pentyloxy]benzoic acid (CBO5OBA) is described. Both acids show an enantiotropic nematic phase attributed to the formation of supramolecular complexes by hydrogen bonding between the benzoic acid units. In addition, CB6OBA provides the first example of hydrogen bonding driving the formation of the twist‐bend nematic phase. The observation of the twist‐bend nematic phase for CB6OBA, but not CBO5OBA, is attributed to the more bent molecular shape of the complexes formed by the former, reinforcing the view that shape is a key factor in stabilizing this new phase. Temperature‐dependent FTIR spectroscopy reveals differences in hydrogen bonding between the two nematic phases shown by CB6OBA which suggest that the open hydrogen‐bonded complexes may play an important role in stabilizing the helical arrangement found in the twist‐bend nematic phase.